2023
DOI: 10.1039/d3ta03192f
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and conduction in metal–organic framework glasses

Milton Chai,
Ruiqi Chen,
Kaijie Xu
et al.

Abstract: Metal-organic frameworks (MOFs) are a group of highly tunable porous materials composed of metal nodes and organic linkers. Although MOF research has predominantly focused on crystalline frameworks, amorphous MOFs with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 123 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…However, in our case, as evidenced from the XPS and XRD analysis, none of the isoreticular Li-MOFs has solvent molecules coordinated to the tetrahedron Li-ion metal centers, where unsaturated OMSs can readily generate by removing the coordinated solvent molecules via inert thermal activation processes. Thus, our thesis hypothesis for the Li + conduction may follow a pore filling mechanism of lithium salts via occupying mobile Li-ions in accessible pores of the framework. , Successive pore filling of lithium salts (LEC) into the framework’s cavities may allow us to verify and establish the Li + conduction in isoreticular Li-MOFs. The differences in ionic conductivities could reveal the subtle effect of their isoreticular framework expansion, thereby varying the pore filling capacity and binding with the framework for the mobile Li-ions.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…However, in our case, as evidenced from the XPS and XRD analysis, none of the isoreticular Li-MOFs has solvent molecules coordinated to the tetrahedron Li-ion metal centers, where unsaturated OMSs can readily generate by removing the coordinated solvent molecules via inert thermal activation processes. Thus, our thesis hypothesis for the Li + conduction may follow a pore filling mechanism of lithium salts via occupying mobile Li-ions in accessible pores of the framework. , Successive pore filling of lithium salts (LEC) into the framework’s cavities may allow us to verify and establish the Li + conduction in isoreticular Li-MOFs. The differences in ionic conductivities could reveal the subtle effect of their isoreticular framework expansion, thereby varying the pore filling capacity and binding with the framework for the mobile Li-ions.…”
Section: Resultsmentioning
confidence: 97%
“…To date, the solid electrolytes such as inorganic and polymer electrolytes exhibit Li + ion hopping mechanisms, which either follow hopping from one coordination site to the vacant nearest site in inorganic solid electrolytes , or follow the segmental motion of the polymer chains, inducing the ligand exchange of Li + and Li + hopping in polymer electrolytes . In MOF-based SSEs, prior research has shown that Li + transport in the framework channels involves complex interactions between cations, anions, and framework segments . For example, a free motion of Li + conduction mechanism involving cationic and anionic interactions has been revealed in MOFs by creating anionic channels via post modifications of OMCs of the MOF framework with anions like ClO 4 – , BF 4 – , NO 3 – , Cl – , and Br – .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations